2017
DOI: 10.1155/2017/9349487
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Nigrostriatal Pathway in the MPTP Mouse Model of Parkinson’s Disease

Abstract: The characteristic brain pathology and motor and nonmotor symptoms of Parkinson's disease (PD) are well established. However, the details regarding the causes of the disease and its course are much less clear. Animal models have significantly enriched our current understanding of the progression of this disease. Among various neurotoxin-based models of PD, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model is the most commonly studied model. Here, we provide an overview of the dynamic changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 70 publications
2
49
0
1
Order By: Relevance
“…Negative interactions on the local volumes of gray and white matter structures suggest persistent injury-induced changes and/or impaired development following repetitive blast injury. Interactions in structures involved with vestibular, dopaminergic nigrostriatal pathway (caudate putamen, substantia nigra), and associated movement pathways point to circuits with selective vulnerability in movement disorders and/or Parkinsonism ( Acosta et al, 2015 ; Huang et al, 2017 ). Furthermore, negative interactions in raphe nuclei (dorsal and median) and the BNST implicate pathways along the hypothalamic-pituitary-adrenal (HPA) axis involved in stress response and mood regulation ( Somerville et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Negative interactions on the local volumes of gray and white matter structures suggest persistent injury-induced changes and/or impaired development following repetitive blast injury. Interactions in structures involved with vestibular, dopaminergic nigrostriatal pathway (caudate putamen, substantia nigra), and associated movement pathways point to circuits with selective vulnerability in movement disorders and/or Parkinsonism ( Acosta et al, 2015 ; Huang et al, 2017 ). Furthermore, negative interactions in raphe nuclei (dorsal and median) and the BNST implicate pathways along the hypothalamic-pituitary-adrenal (HPA) axis involved in stress response and mood regulation ( Somerville et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the regimen of MPTP administration was defined based on the dynamic changes in the nigrostriatal pathways [ 29 ]. We stablished three MPTP administrations (3 doses, at 2-h intervals in 1 day) distributed in three time-points.…”
Section: Discussionmentioning
confidence: 99%
“…3h, i). Moreover, MPTP-treated mice usually develop rapid microgliosis in the striatum and SN [21]. Interestingly, we found that the expression of Iba1 (a marker of microglia) in the SN was signi cantly attenuated in MPTP-treated Maged1 KO mice (Fig.…”
Section: Resultsmentioning
confidence: 72%